TYPE 1/TYPE 2 CYTOKINE SERUM LEVELS AND ROLE OF INTERLEUKIN-18 IN CHILDREN WITH STEROID SENSITIVE NEPHROTIC SYNDROME - Sherein A. Shalaby; Howaida M. Al-Edressi; Shereen A. El-Tarhouny; Mohamed Fath EL-Bab; Mohamed A. Zolaly (European Scientific Journal, ESJ, 2013)
Aims: In view of the conflicting evidence of helper T cell type 1 (Th1) or type 2 (Th2) pattern of cytokine synthesis in steroid sensitive nephrotic syndrome (SSNS) this study aims to assess type-1 /type-2 cytokines in different stages of SSNS and define the potent involvement of IL- 18 Methodology: We prospectively studied thirty children with steroid sensitive nephrotic syndrome (SSNS), aged 2–12 years. Thirty children were in active stage before treatment initiation, the same 30 children in remission still on steroids; 21/30 in remission off steroids as well. The control group Included 30 healthy age and sex matched siblings. Using ELISA technique we assessed serum levels of Serum, IL-2, IFN-γ, ΙL-4, IL-13 and IL-18 in different stages of the disease and in controls. Results: IL-2 levels were not significantly different in children of all disease stages of SSNS and controls (p > 0.05). Levels of IL-4, IL-13 and IL-18 were significantly higher in the active stage of SSNS compared with the remission stages and controls (p<0.05). But, serum IFN-γ was significantly lower in children with active disease compared with remission stages and controls (p<0.05). In children with SSNS, of all disease stages, serum levels of IL-18 were significantly correlated with both IL-4 and IL-13 (r = 0.72 and p<0.0001, r = 0.82 and p<0.0001, respectively). Conclusion: Children with active SSNS seem to have a shift to type-2 cytokine production, and IL-18 expression is significantly correlated with this type-2 immune response.